CREATE a CUSTOMER LOYALTY In TRAVEL SECTOR - Siti Maemunah (Business and Entrepreneurial Review, 2020)
Research related to loyal customers in the travel industry. The travel industry adopts strategic e-marketing, technological innovation, trust and value to customers. Customers feel satisfied, thus creating customer loyalty. The methodology for this writing was to distribute questionnaires to 240 travel decision makers (managers / directors / owners). The data were analyzed through the SEM research hypothesis using SPSS / AMOS applied to the relationship and hypothesis testing. The results showed that strategic e-marketing, technological innovation, trust and value on customers had a direct and significant positive effect on satisfaction. Customer satisfaction has a direct and significant positive effect on customer loyalty. The implication of writing helps marketing managers to encourage customer satisfaction by fostering trust and value, creating customer loyalty in the travel sector. This novelty research provides new insights in the development of e-marketing strategies and technological innovation has been recognized as a developing concept that has received intense attention from both literature reviews and practitioners. In addition, further empirical research is still needed to investigate all-digital marketing insights around the world. To enrich the theoretical point of view of the proposed model, further research can carry out a comparative study between industry and developing countries.